Youtube and music online culture and everyday life - Rogers, Holly ca. 20./21. Jh; Freitas, Joana; Porfírio, João Francisco (Bloomsbury Academic, 2023)
YouTube has afforded new ways of documenting, performing and circulating musical creativity. This first sustained exploration of YouTube and music shows how record companies, musicians and amateur users have embraced YouTube's potential to promote artists, stage performances, build artistic (cyber)identity, initiate interactive composition, refresh music pedagogy, perform fandom, influence musical tourism and soundtrack our everyday lives. Speaking from a variety of perspectives, musicologists, film scholars, philosophers, new media theorists, cultural geographers and psychologists use case studies to situate YouTube as a vital component of contemporary musical culture
Hier auch später erschienene, unveränderte Nachdrucke
Keywords: Musikkonsum; YouTube; Medienkultur; YouTube (Electronic resource); Music and the Internet; Music; Aufsatzsammlung